Widerstände, Visionen und Geistführung bei Paulus - Kowalski, Beate (Zeitschrift für katholische Theologie, 2003)
The article deals with some Lukan perspectives of the interpretation of Paul the Apostle. The conversion of Paul in Acts 9 is the prologue containing central themes of the Lukan missionary theology. Four main aspects characterize him fforn the Lukan point of view: double mission to Jews and Gentiles, resistances, visions, and guidance by the Holy Spirit accompany his journeys from the very beginning, his conversion in Damascus, tili the end of his activities in Rome. These aspects are developed within the following chapters narrating the missionary journeys. Sufferings, but as well continuous revelations by Christ accompany Paul's way in the book of Acts, especially at crucial passages. Are resistances, visions, and guidance by the Holy Spirit signs of a certain coincidence or an act of divine providence? This question cannot be answered objectively. Luke argues that God had a plan with Paul and that his varied missionary efforts would not have been possible without divine providence. The resistances against Paul were insurmountable from a human viewpoint. Similarities and differences between Luke's interpretation of Paul and his own writings are mentioned in passing. Both Paul and Luke are convinced that without God's guidance and support the missionary program never would have been successful.